Kajian Model Pembelajaran Kooperatif Tipe STAD (Student Teams Achievement Division) Dalam Upaya Meningkatkan Efektifitas Proses Belajar Mengajar Akuntansi - Yudho Ramafrizal; Teni Julia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
The purpose of this research is to know how the result of applying Adjustment journal concept through cooperative learning model type STAD (Student Teams Achievement Division) in class XI IPS 3 SMAN 6 Bandung, to know how the effectiveness of teaching and learning process in accounting subjects subject of adjustment journal by using model STAD type cooperative learning, STAD type cooperative learning model (Student Teams Achievement Division) in order to overcome the saturation and difficulties experienced by students of class XI IPS 3 SMAN 6 Bandung. The research methodology used is descriptive research. The subjects of the study were students of class XI IPS 3 SMAN 6 Bandung. Data collection techniques in this study were conducted with documentation and questionnaire / questionnaire. The results of the application of STAD type cooperative learning model in the subject of adjusting journal shows 3.94 results that are in good category. the results of research from the effectiveness of teaching and learning process on the subjects of accounting showed 3.99 results are in either category. STAD type cooperative learning model in overcoming the saturation and learning difficulties learners showed the average result classical is 3.97 which is in good category and the level of effectiveness of teaching and learning process of 79.94% of the data obtained based on the questionnaire distributed to 36 respondents . Based on the findings in the field, the conclusion of the results of this study is STAD type cooperative learning model can overcome the saturation and learning difficulties faced by learners. Therefore this learning model can be used for learning so that teaching and learning process can be implemented effectively.